Colour in art - Gage, John 1938-2012 (Thames & Hudson, 2023)
The complex phenomenon of colour has received detailed attention from the perspectives of physics, chemistry, physiology, psychology, linguistics and philosophy. However, the people who work most closely with colour – artists – have rarely been canvassed for their opinions on this mysterious subject. John Gage sets out to address this omission by focusing on the thoughts and practices of artists. Colour in Art is concerned with the history of colour, but is not itself a history; instead each chapter develops a theme from a different scientific discipline, as seen from the viewpoint of such diverse artists such as Wassily Kandinsky, Vincent van Gogh, Sonia Delaunay, Bridget Riley and Clifford Possum Tjapaltjarri. Drawing on examples through the ages, from ancient times to the present, the many topics covered include flags, synaesthesia, Theosophy, theatre design, film, chromotherapy and chromophobia. Featuring a new foreword by art writer Kelly Grovier outlining contemporary developments in the study of colour, and an updated bibliography, this new edition of this classic text offers a wide-ranging and engaging introduction to the place and power of colour in life and art
First published in 2006 in the United Kingdom by Thames & Hudson Ltd, 181A High Holborn, London WC1V 7QX
Keywords: Farbe; Kunst; Ästhetik; Color in art; Art / Philosophy